Exploration cognitive, logical, and metacognitive abilities of biology education students across academic semesters - Safira Permata Dewi; Riandi Riandi; Nuryani Rustaman (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2026)
Cognitive, logical, and metacognitive abilities are core competencies for preservice science teachers; however, comprehensive cross-semester mapping of these abilities using an integrated approach remains limited. This study aimed to explore the profiles and interconnections of cognitive, logical thinking, and metacognitive abilities of biology education students across early and mid-academic semesters. A mixed-method design was employed. Quantitative data were collected from 64 second- and fourth-semester students through a Marzano-based cognitive test, the Test of Logical Thinking (ToLT), and the Metacognitive Awareness Inventory (MAI), followed by qualitative exploration using open-ended questionnaires and semi-structured interviews with 10 purposively selected students. Quantitative data were analyzed descriptively, while qualitative data were examined using thematic analysis to explain and elaborate the quantitative results. The findings revealed similar patterns across both semesters, characterized by low achievement in error analysis (35.42%–40.63%), experimentation (45.83%–50.00%), control of variables and correlational reasoning in ToLT (≤38%), as well as planning and evaluation aspects of metacognitive regulation (79.05-80.09%). Qualitative findings indicated that students tended to focus on procedural aspects and showed limited ability to conduct conceptual error analysis and experimental evaluation. The consistency of these patterns across semesters suggests that predominantly recipe-based learning experiences have not sufficiently supported the development of higher-order reasoning and metacognitive reflection. This study concludes that inquiry-based instructional designs that explicitly integrate error analysis, generalization, variable control, and metacognitive reflection are necessary to enhance learning quality and better prepare future science teachers.Abstrak. Kemampuan kognitif, berpikir logis, dan metakognitif merupakan kompetensi inti yang harus dikembangkan secara terintegrasi pada calon guru sains, namun pemetaan ketiga kemampuan tersebut lintas semester masih jarang dikaji secara komprehensif, khususnya dengan pendekatan campuran. Penelitian ini bertujuan untuk mengeksplorasi profil dan keterkaitan kemampuan kognitif, berpikir logis, dan metakognitif mahasiswa pendidikan biologi pada semester awal dan menengah. Penelitian menggunakan desain mixed-method dengan strategi explanatory sequential. Sebanyak 64 mahasiswa semester 2 dan 4 dipilih secara acak untuk pengumpulan data kuantitatif melalui tes kognitif berbasis taksonomi Marzano, Test of Logical Thinking (ToLT), dan Metacognitive Awareness Inventory (MAI), yang kemudian diperdalam melalui kuesioner terbuka dan wawancara semi-terstruktur terhadap 10 mahasiswa terpilih. Data kuantitatif dianalisis secara deskriptif, sedangkan data kualitatif dianalisis menggunakan analisis tematik untuk menjelaskan dan memperkuat temuan kuantitatif. Hasil penelitian menunjukkan pola yang relatif serupa pada kedua semester, dengan capaian rendah pada indikator analisis kesalahan (35,42%–40,63%), eksperimen (45,83%–50,00%), pengontrolan variabel dan penalaran korelasional pada ToLT (≤38%), serta perencanaan dan evaluasi dalam regulasi metakognitif (79.05%–80.09%%). Temuan kualitatif mengungkap bahwa mahasiswa cenderung berfokus pada prosedur teknis dan belum mampu melakukan analisis kesalahan serta evaluasi eksperimen secara konseptual. Kesamaan pola lintas semester mengindikasikan bahwa pengalaman belajar yang dominan bersifat resep belum secara optimal melatihkan penalaran tingkat tinggi dan refleksi metakognitif. Penelitian ini menyimpulkan bahwa diperlukan desain pembelajaran berbasis inkuiri yang secara eksplisit mengintegrasikan pelatihan analisis kesalahan, generalisasi, pengontrolan variabel, dan refleksi metakognitif untuk meningkatkan kualitas pembelajaran dan kesiapan calon guru di masa depan.